Analisis Proses Penyidikan Pelaku Tindak Pidana Pencurian Terhadap Benda Sitaan - Elfina Dwi Rahayu; Margo Hadi Pura (Jurnal Ilmiah Wahana Pendidikan, 2023)
The role of the State Storage for Confiscated Objects (Rupbasan) is one of the most important things. The State Storage for Confiscated Objects is a place where objects confiscated by the State for the purposes of the judicial process are stored. This investigation process was carried out to find out more about the case of theft of confiscated objects that occurred at the State Storage for Confiscated Objects (Rupbasan). This discussion shows that for the process of investigating a criminal case of theft of confiscated state goods, the process and implementation are the same as the implementation of investigations of other crimes as used by investigators. With the existence of cases of criminal acts of theft that occurred in Rupbasan, the implementation of the investigation process by investigators related to the theft of confiscated state objects has been regulated based on the provisions contained in Kapolri Regulation No. 6 of 2019 Article 10 paragraph (1) concerning Investigation of a Criminal Case, especially in Cases of Theft. Then, there is functional coordination that will be carried out by the investigator and the Rupbasan are interrelated, which later this coordination will be aimed at the perpetrators of the crime of theft. This coordination can be divided into 4 parts, namely: (a) Functional coordination is coordination carried out in the form of calling for information related to the crime of theft that occurred in the Storage House; (b) Functional coordination is also coordination carried out in the form of monitoring or observation; (c) Functional coordination is a form of coordination that is carried out through the holding of cases where the crime of theft occurred at the Object Storage House; and (d) Explanation regarding Functional coordination is also coordination carried out by carrying out the process of securing an item of evidence from theft by the suspect.